Differentiation of ductal carcinoma in-situ from benign micro-calcifications by dedicated breast computed tomography. Issue 1 (January 2016) - Aminololama-Shakeri, Shadi; Abbey, Craig K.; Gazi, Peymon; Prionas, Nicolas D.; Nosratieh, Anita; Li, Chin-Shang; Boone, John M.; Lindfors, Karen K.
Highlights: CEbCT is an emerging imaging modality that shows potential for detecting and diagnosing DCIS. DCIS lesions are more readily visualized on contrast-enhanced breast CT than benign micro-calcifications ( p < 0.0001). Conspicuity of DCIS calcifications is not significantly different on CEbCT and mammography ( p = 0.69). The enhancement differential between benign and malignant calcifications on CEbCT allows for quantitative as well as qualitative assessment of these lesions. CEbCT may have an advantage over mammography by reducing false positive biopsies of micro-calcifications. Abstract: Purpose: Compare conspicuity of ductal carcinoma in-situ (DCIS) to benign calcifications on unenhanced (bCT), contrast-enhanced dedicated breast CT (CEbCT) and mammography (DM). Methods and materials: The institutional review board approved this HIPAA-compliant study. 42 women with Breast Imaging Reporting and Data System 4 or 5 category micro-calcifications had breast CT before biopsy. Three subjects with invasive disease at surgery were excluded. Two breast radiologists independently compared lesion conspicuity scores (CS) for CEbCT, to bCT and DM. Enhancement was measured in Hounsfield units (HU). Mean CS ± standard deviations are shown. Receiver operating characteristic analysis (ROC) measured radiologists' discrimination performance by comparing CS to enhancement alone. Statistical measurements were made using ANOVA F -test, Wilcoxon rank-sum test and robust linear regression analyses. Results: 39 lesions (17 DCIS, 22 benign) were analyzed. DCIS (8.5 ± 0.9, n = 17) was more conspicuous than benign micro-calcifications (3.6 ± 2.9, n = 22; p < 0.0001) on CEbCT. DCIS was equally conspicuous on CEbCT and DM (8.5 ± 0.9, 8.7 ± 0.8, n = 17; p = 0.85) and more conspicuous when compared to bCT (5.3 ± 2.6, n = 17; p < 0.001). All DCIS enhanced; mean enhancement (90HU ± 53HU, n = 17) was higher compared to benign lesions (33 ± 30HU, n = 22) ( p < 0.0001). ROC analysis of the radiologists' CS showed high discrimination performance (AUC = 0.94) compared to enhancement alone (AUC = 0.85) ( p < 0.026). Conclusion: DCIS is more conspicuous than benign micro-calcifications on CEbCT. DCIS visualization on CEbCT is equal to mammography but improved compared to bCT. Radiologists' discrimination performance using CEBCT is significantly higher than enhancement values alone. CEbCT may have an advantage over mammography by reducing false positive examinations when calcifications are analyzed.